Intracranial Volume and Head Circumference in Children with Unoperated Syndromic Craniosynostosis. Issue 5 (November 2018) - Breakey, Richard William Francis; Knoops, Paul G. M.; Borghi, Alessandro; Rodriguez-Florez, Naiara; O'Hara, Justine; James, Gregory; Dunaway, David J.; Schievano, Silvia; Jeelani, N. U. Owase
Abstract : Background: When analyzing intracranial volume gain resulting from operative intervention in craniosynostosis, it is necessary to understand the underlying growth. The authors sought to create comprehensive intracranial volume and occipitofrontal circumference growth charts, as measured on unoperated craniosynostotic children, and aimed to investigate whether intracranial volume and occipitofrontal circumference could act as proxy measures for each other. Methods: All preoperative Great Ormond Street Hospital patients with a diagnosis of Apert, Crouzon-Pfeiffer, or Saethre-Chotzen syndrome from the year 2004 onward were considered for this study. A control group of unaffected Great Ormond Street Hospital patients were also measured. Intracranial volume and occipitofrontal circumference were measured on the same scans. To study correlation between intracranial volume and occipitofrontal circumference, logarithmic fits were assessed. Results: One hundred forty-seven craniosynostotic children with 221 preoperative scans were included (81 Apert, 81 Crouzon, 31 Pfeiffer, and 28 Saethre-Chotzen). The control group comprised 56 patients with 58 scans. Apert intracranial volume curves were significantly larger than those of other syndromes from 206 days onward; occipitofrontal circumference curves were not significantly different. The correlation coefficient between intracranial volume and occipitofrontal circumference was R 2 = 0.87 for all syndromes combined and R 2 = 0.91 for the control group. Conclusions: Apert syndrome children have a larger intracranial volume than children with other syndromic craniosynostotic conditions and unaffected children but maintain a similar occipitofrontal circumference. This study demonstrates high correlation between intracranial volume and occipitofrontal circumference with clinical care implications. The authors' reference growth curves can be used to monitor intracranial volume change over time and correct operative change for underlying growth. Abstract : Supplemental Digital Content is available in the text.